2023
DOI: 10.1021/acsami.3c10017
|View full text |Cite
|
Sign up to set email alerts
|

HVHC-ESD-Induced Oxygen Vacancies: An Insight into the Phenomena of Interfacial Interactions of Nanostructure Oxygen Vacancy Sites with Oxygen Ion-Containing Organic Compounds

Shahab Sharifi Malvajerdi,
Shahrzad Aboutorabi,
Azita Shahnazi
et al.

Abstract: The challenging environmental chemical and microbial pollution has always caused issues for human life. This article investigates the detailed mechanism of photodegradation and antimicrobial activity of oxide semiconductors and realizes the interface phenomena of nanostructures with toxins and bacteria. We demonstrate how oxygen vacancies in nanostructures affect photodegradation and antimicrobial behavior. Additionally, a novel method with a simple, tunable, and cost-effective synthesis of nanostructures for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 83 publications
0
1
0
Order By: Relevance
“…Over the past few decades, numerous studies have emphasized the physiochemical stability and ease of availability of metal oxide semiconductors. Amid these materials, zinc oxide as a wide band gap (3.3 eV) semiconductor with optical properties similar to GaN and large exciton binding (60 meV) is a great candidate for short-wavelength optoelectronics devices. Bottom-up engineering of textured nanostructure blade-coated ZnO thin films on low-cost substrates is commonly eye-catching because of the exceptional oxygen physisorption and photodesorption behavior on their surface and light trapping capabilities in UV detection applications. Soci et al reported that ZnO nanorods exhibit high internal photoconductive gain and superior photoresponsivity under UV exposure compared to their bulk counterparts .…”
Section: Introductionmentioning
confidence: 99%
“…Over the past few decades, numerous studies have emphasized the physiochemical stability and ease of availability of metal oxide semiconductors. Amid these materials, zinc oxide as a wide band gap (3.3 eV) semiconductor with optical properties similar to GaN and large exciton binding (60 meV) is a great candidate for short-wavelength optoelectronics devices. Bottom-up engineering of textured nanostructure blade-coated ZnO thin films on low-cost substrates is commonly eye-catching because of the exceptional oxygen physisorption and photodesorption behavior on their surface and light trapping capabilities in UV detection applications. Soci et al reported that ZnO nanorods exhibit high internal photoconductive gain and superior photoresponsivity under UV exposure compared to their bulk counterparts .…”
Section: Introductionmentioning
confidence: 99%